Corpus Aligner (CorAl) Evaluation on English- Croatian Parallel Corpora - Seljan, Sanja (Array, 2010)
An increasing demand for new language resources of recent EU members and accessing countries has in turn initiated the development of different language tools and resources, such as alignment tools and corresponding translation memories for new languages pairs. The primary goal of this paper is to provide a description of a free sentence alignment tool CorAl (Corpus Aligner), developed at the Faculty of Electrical Engineering and Computing, University of Zagreb. The tool performs paragraph alignment at the first step of the alignment process, which is followed by sentence alignment. Description of the tool is followed by its evaluation. The paper describes an experiment with applying the CorAl aligner to a English-Croatian parallel corpus of legislative domain using metrics of precision, recall and F1- measure. Results are discussed and the concluding sections discuss future directions of CorAl development.